DETERMINANTS ON CHANGES IN ENERGY INTENSITY OF MANUFACTURING SECTOR IN INDONESIA - , Bambang Nugroho, S.E.; , Prof. Shinji Kaneko ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study analyzed the characteristic of energy intensity in the manufacturing sector during 1990-2000, the underlying forces behind its changes, and the sources of those forces using index decomposition analysis (IDA). Subsequently, this research used panel data analysis to explore some options available to improve manufacturing energy intensity. IDA suggested that there were real energy efficiency improvements in the manufacturing sector during 1990-1993 and 1993-1996. These improvements were shown by sub-sector intensity effect, which strongly pulled total energy intensity down. The analysis also indicated that the strength of both forces mostly came from the food, beverages, and tobacco industries. The estimation result from panel data analysis suggests that electricity price, ratio of product exported, and labor productivity negatively affect energy intensity. It means that increasing those factors will enhance energy intensity level in the manufacturing sector.